Análisis crítico del Derecho Constitucional desde la perspectiva del nuevo constitucionalismo latinoamericano. Entrevista a Rubén Martínez Dalmau - Monge Morales, Gonzalo J. (2015)
What do the current Constitutions of Bolivia, Ecuador, Colombia and Venezuela   have in common? These are all part of what is known asthe new Latin American constitutionalism, a recenttheory  of  Constitutional  Law  that  offers  a new approach to analize the role of constitutionalism inthe present times.THĒMIS-Law Review had the opportunity to interview the main representative of this Latin American constitutionalism, with regard to what this new proposal is about, the solutions it presents, the challenges it faces, as well as the reading it offers about constitutional phenomenons and Constitutional Law institutions.